Right atrial morphology and function in patients with systemic sclerosis compared to healthy controls: a two-dimensional strain study. Issue 7 (July 2016) - D'Andrea, Antonello; D'Alto, Michele; Di Maio, Marco; Vettori, Serena; Benjamin, Nicola; Cocchia, Rosangela; Argiento, Paola; Romeo, Emanuele; Di Marco, Giovanni; Russo, Maria; Valentini, Gabriele; Calabrò, Raffaele; et al.
Abstract Enlargement and dysfunction of the right atrium might be an early sign for pulmonary hypertension in systemic sclerosis (SSc). This is the first study to analyse right atrial morphology and function in SSc patients compared to healthy controls by speckle-tracking two-dimensional strain echocardiography (2DSE) at rest and during exercise. Furthermore, right atrial function was correlated with further clinical findings. Adult patients with SSc for >3 years (n = 90) and 55 age- and gender-matched healthy controls underwent a panel of non-invasive assessments including transthoracic echocardiography, pulsed Doppler myocardial imaging and 2DSE at rest and during exercise. Furthermore, serological tests and high-resolution chest computed tomography were performed. SSc patients showed significant impairment of right atrial function and the right atrial enlargement, measured by 2DSE at rest and during exercise compared to controls (bothp < 0.001). These findings were more evident in SSc patients with pulmonary fibrosis (p < 0.001) and in patients with high pulmonary artery systolic pressures (PAPs) during exercise. In the SSC patients, right atrial lateral strain was significantly associated with PAPs during effort, right atrial area, left ventricle stroke volume and inferior vena cava diameter using multivariable analysis. The findings of this study suggest that a high proportion of SSc patients reveal right atrial dysfunction even without manifest pulmonary hypertension. Impaired right atrial function occurred mostly in patients with pulmonary fibrosis and/or elevated PAPs during exercise, was independently associated with prognostic factors and may therefore be useful for risk stratification. Further studies are needed to analyse if right atrial dysfunction assessed by 2DSE may help to improve early diagnosis of pulmonary hypertension.